2024
DOI: 10.7759/cureus.51431
|View full text |Cite
|
Sign up to set email alerts
|

Mesh Extraction Surgery and Laser Treatment for Pain After Mid-Urethral Sling Surgery: A Case Series

Nobuo Okui,
Machiko.Aurora Okui

Abstract: Stress urinary incontinence (SUI) is the leakage of urine due to abdominal pressure. The primary surgical approach involves the insertion of a mid-urethral sling (MUS) with a mesh, which can occasionally lead to post-operative pain. To address complications, MUS removal is often necessary. We hypothesize that a nonablative erbium:yttrium aluminum garnet (Er:YAG) laser combined with vagina (vaginal erbium laser (VEL)) and urethra (urethra erbium laser (UEL)) treatments could be a post-MUS removal option. A stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 18 publications
0
1
0
Order By: Relevance
“…It has been reported that TVT may worsen symptoms of OAB in some cases [14]. The polypropylene mesh used in TVT and TOT has been reported to cause pain in some patients and form pathological granulomas [15]. In contrast, laser treatment has been reported to be safe with fewer side effects, and there is evidence of its efficacy in randomized controlled trials) [16,17].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that TVT may worsen symptoms of OAB in some cases [14]. The polypropylene mesh used in TVT and TOT has been reported to cause pain in some patients and form pathological granulomas [15]. In contrast, laser treatment has been reported to be safe with fewer side effects, and there is evidence of its efficacy in randomized controlled trials) [16,17].…”
Section: Discussionmentioning
confidence: 99%
“…Pain was assessed using a Visual Analog Scale (VAS) [13,15]. For patients with urinary incontinence, evaluations were conducted using the 1-hour pad test [13,28], the International Consultation on Incontinence Questionnaire-Short Form (ICIQ-SF) [13], and the Overactive Bladder Symptom Score (OABSS) [13]. Patients with fecal incontinence were assessed using the St. Mark's Score [27].…”
Section: Clinical Evaluationmentioning
confidence: 99%
“…However, research on the pathology of the mesh placed at the sacral colpopexy site in LSC is lacking in previous studies. Understanding the long-term effects and degradation of mesh, as well as the body's reaction to it, remains limited [11][12][13]. Further research in this area is necessary to improve treatment methods [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…SUI affects a significant proportion of women, significantly diminishing their quality of life 7 10 . A common treatment is mid-urethral sling (MUS) procedures using polypropylene mesh, but this method can lead to postoperative pain, foreign body reactions, inflammation, and even the emergence or worsening of Urgency Urinary Incontinence (UUI) 11 13 . Given these issues, Vaginal Erbium Laser (VEL) therapy has gained attention as a non-ablation alternative 14 18 .…”
Section: Introductionmentioning
confidence: 99%